Brillaran como estrellas... - Gutiérrez, Enrique, O.F.M (Ediciones Aldecoa, 1981)
Santa Beatriz e Silva -- Juana de San Miguel -- María de Ayala -- Inés de San Pablo -- María de San Pablo -- María de Jesús -- María de Jesús de Agreda -- Custoida María -- María Rosa -- Patrocinio de las Llagas -- María Angeles Sorazu -- Juana Angela del Brasil -- Mártires de España -- Convento el Pardo -- Convento San José